1997
DOI: 10.1097/00000374-199704000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Hearing, Language, Speech, Vestibular, and Dentofacial Disorders in Fetal Alcohol Syndrome

Abstract: Fetal alcohol syndrome (FAS) is characterized by congenital anomalies traditionally associated with hearing disorders. The present study sought to (a) evaluate possible central hearing loss; (b) verify and extend previous observations on sensorineural and conductive hearing losses; (c) evaluate possible vestibular disorders; (d) examine the relationships between hearing, speech, language, vestibular, and dentofacial disorders in FAS patients; and (e) evaluate the influence of patient age, race, and gender on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 0 publications
0
65
3
Order By: Relevance
“…The effect of alcohol on a developing fetus place individuals with prenatal alcohol exposure at increased risk for a range of medical problems, including cardiac problems, skeletal defects, sensory deficits, and dental problems [Church et al, 1997;Autti-R€ am€ o et al, 2006]. Other research has documented that children with FASDs are hospitalized more frequently than nonexposed children [Kvigne et al, 2004].…”
Section: Medical Issuesmentioning
confidence: 99%
“…The effect of alcohol on a developing fetus place individuals with prenatal alcohol exposure at increased risk for a range of medical problems, including cardiac problems, skeletal defects, sensory deficits, and dental problems [Church et al, 1997;Autti-R€ am€ o et al, 2006]. Other research has documented that children with FASDs are hospitalized more frequently than nonexposed children [Kvigne et al, 2004].…”
Section: Medical Issuesmentioning
confidence: 99%
“…Studies of people with FAS showed significant weakening of the central auditory [13] in all patients (100%). As it is apparent from the above tests that delayed speech development in case of children with FAS is a result of central auditory processing disorder [14], as well as damage to conductive hearing, receiving, or a mixed one.…”
Section: Therapeutic Proceduresmentioning
confidence: 96%
“…Subjects with this syndrome, present with a high prevalence of dental anomalies and speech pathologies that frequently require early intervention 5 . A high rate of temporo-mandibular joint disorders has also been reported 5 .…”
Section: What Are the Repercussions On Orthodontic Treatment?mentioning
confidence: 99%
“…-The majority of these children have disorders in the ENT area and vestibular dysfunction is common 5 …”
Section: What Are the Repercussions On Orthodontic Treatment?mentioning
confidence: 99%